Top Answer

First, factor out the k. So, k(4+2) = 30

or 6k = 30

Then divide by 6. k = 30/6 = 5

So k = 5.

🙏

0🤨

0😮

0😂

0Loading...

If by K2 you are not referring to the mountain, the distributive property of multiplication tells us K * 2 = 2 * K.Therefore: K2 + 2K + 4K = 2K + 2K + 4K = 8K

(2k + 3) (2k + 3)

It can be simplified to: 9k

2k - 3l

4k + 24 = 6k - 10 subtract 4k from each side 4k - 4k + 24 = 6k - 4k - 10 24 = 2k - 10 add 10 to each side 10 + 24 = 2k - 10 + 10 34 = 2k divide each side integers by 2 17 = k ------------check 4(17) + 24 = 6(17) - 10 68 + 24 = 102 - 10 92 = 92 checks

-4k + 10 - k + 2 = 2k + 4k + 18Combine all the 'k' terms on the left side:-5k + 10 + 2 = 2k + 4k + 18Combine all the 'k' terms on the right side:-5k + 10 + 2 = 6k + 18Combine the numerical terms on the left side:-5k + 12 = 6k + 18Add 5k to each side:12 = 11k + 18Subtract 18 from each side:-6 = 11kDivide each side by 11:k = -6/11

Let even be of the form 2k and odd be of the form 2k+1. Then odd * even becomes 2k*2k+1, or 4k^2 +2k. This can be written as 2(k^2 + k), which is of the form 2k. Therefore, odd X even equals even.

4k-91h

q=4k+4uImproved Answer:-If: Q = 4k+4uThen: k = (4u-Q)/-4

1k/2k, 2k/4k, 3k/6k and so on.

k=-2

-4k-2=10 -4k=10+2 -4k=12 k=-3

J = K+6 K + J = 4K Replace J in the second equation K + (K + 6) = 4K K + K + 6 = 4K 2K + 6 = 4K Subtract 2K from each side 6 = 2K divide both sides by 2 3 = K So, Keisha is 3 and therefore John is 9

what is -5+3+4k=-115

Take 3k from both sides to get k-3 equals 4, so k is 7

4k-7 = 7 4k = 14 k = 3.5 or k = 7/2

I was just told between $2K and $4K at Cornell In Stamford CT

8-4k = 40 (4k-8) - 8 = 40-8 4k = 32 4k/4 = 32/4 k =8

9k + 8

Equation: x^2 +2kx +10x +k^2 +5 = 0 Using the discriminant: (2k +10)^2 -4*1*(k^2 +5) = 0 Multiplying out the brackets: 4k^2 +40K +100 -4k^2 -20 = 0 Collecting like terms: 40k +80 = 0 => 40k = -80 => k = -80/40 Therefore the value of k = -2

4k

31 = 3-4k 31-3 = -4k 28 = -4k Divide both sides of the equation by -4 to find the value of k: k = -7

7k + 4 + 4k - 9 - 5k (7k + 4k - 5k) + (4 - 9) 6k + -5 6k - 5

k = 2

3k+4m+2